2007
DOI: 10.1539/joh.49.32
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of Immune Functions and Oxidative Status Induced by Noise Stress

Abstract: Modulations of Immune Functions andOxidative Status Induced by Noise Stress: KuiCheng ZHENG, et al. Department of Environmental and Preventive Medicine, Faculty of Medicine, University of the Ryukyus-Noise has long been realized as an environmental stress causing physiological, psychological and behavioral changes in humans. The aim of the present study was to determine the effect of acute or chronic noise stress on both cellular and humoral immune responses and oxidative status. BALB/c mice were exposed to 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 26 publications
(25 reference statements)
1
42
0
1
Order By: Relevance
“…PBMCs are more sensitive than neutrophils in intense exercise-induced oxidative damage (Sureda et al 2005) and are useful tools as markers reflecting the systemic symptoms of oxidative stress under physical and mental stimulation (Aslan et al 2006;Fedeli et al 2007;Zalata et al 2007;Zheng and Ariizumi 2007). PBMCs are utilized in the present study; they are sensitive to hydrogen-peroxide-induced oxidative stress and are also highly susceptible in their response to heat-shock-responseassociated protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs are more sensitive than neutrophils in intense exercise-induced oxidative damage (Sureda et al 2005) and are useful tools as markers reflecting the systemic symptoms of oxidative stress under physical and mental stimulation (Aslan et al 2006;Fedeli et al 2007;Zalata et al 2007;Zheng and Ariizumi 2007). PBMCs are utilized in the present study; they are sensitive to hydrogen-peroxide-induced oxidative stress and are also highly susceptible in their response to heat-shock-responseassociated protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have also shown that different kinds of stressors may induce or inhibit type 1 diabetes in different experimental models of the disease [7]. Noise pollution is one of the harmful environmental factors for humans when it is higher than normal, could adversely affects to health [8,9]. Noise as an environmental stress causes physiological and psychological changes in humans [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors observed a significant increase of TH mRNA and PNMT mRNA levels in the spleen of animals exposed to acute and short-term stress [17,18] . Zheng and Atiizumi [29] demonstrated that acute exposure to noise stress may enhance immune response, whereas chronic exposure to the same stress may suppress both cellular and humoral immune functions. They hypothesized that the effect of acute and chronic noise stress on immune functions might be related to a neuroendocrine modulation.…”
Section: Discussionmentioning
confidence: 99%